Addressing Social Issues Using Humors in Mayat (1978) Dramatic Text by Hatta Azad Khan - Abdul Walid Ali; Saad Omar; Muhammad Faisal Bin Ahmad (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2022)
Objective: In the dramatic world, humour has been part of releasing tension for readers. Hatta Azad Khan is a renowned Malaysian dramatist who always addresses social issues in his writings. Mayat (1978) is one of his prominent writings that uses this technique by questioning capitalism and people, innuendo and money, and distrust using humour in the dramatic text. Post-1969, Sino-Malay sectarian violence, also known as the 13 May incident in Malaysia, has presented arts differently compared to early Malaysia's independence. Most writings in the post-13 May incident used symbolism and did not address issues literally. The writings also apply to Hatta's writings. The sensitivity of the racial tension has to be appropriately addressed since it resulted in a declaration of Malaysia's national emergency in the same year. Therefore, writing issues has to be done in some discreet inquiries. Methodology: This qualitative research will analyse dramatic text and use Mayat (1978) as a subject study. Techniques used by the dramatist in addressing issues and humour will be explored to learn the writer's thoughts about social studies using drama and theatre as a medium. Findings: Two main ideas in Hatta's writing are social space and social interpretation. The script is an imagination of the writer in a creative way discussing social issues. The intellectual discourse is done subtly in his writing without denying humour. Since both issues are always relevant, especially social space, Hatta's works are always performed by theatre productions even though the writing is done in the 70s. Implications: As a social critic, Hatta uses drama and theatre as a medium of expression. More writings about social issues with good writing like Hatta's works are needed in the future to open more forums since addressing them is usually evergreen.